Activity-Dependent Genes in Mouse Olfactory Sensory Neurons - Fischl, Adrian M. (Oxford University Press, 2014)
Activity-dependent survival of olfactory sensory neurons (OSNs) may allow animals to tune their olfactory systems to match their odor environment. Activity-dependent genes should play important roles in this process, motivating experiments to identify them. Both unilateral naris occlusion of mice for 6 days and genetic silencing of OSNs decreased S100A5, Lrrc3b, Kirrel2, Slc17a6, Rasgrp4, Pcp4l1, Plcxd3, and Kcnn2 while increasing Kirrel3. Naris occlusion also decreased Eml5, Ptprn, and Nphs1. OSN number was unchanged and stress-response mRNAs were unaffected after 6 days of naris occlusion. This leaves odor stimulation as the most likely cause of differential abundance of these mRNAs, but through a mechanism that is slow or indirect for most because 30–40min of odor stimulation increased only 3 of 11 mRNAs decreased by naris occlusion: S100A5, Lrrc3b, and Kirrel2. Odorant receptor (OR) mRNAs were significantly more variable than the average mRNA, consistent with difficulty in reliably detecting changes in these mRNAs after 6 days of naris occlusion. One OR mRNA, Olfr855, was consistently decreased, however. These results suggest that the latency from the cessation of odor stimulation to effects on activity-dependent OSN survival must be a week or more in juvenile mice.